Does social media marketing as moderating relationship between intellectual capital and organizational sustainability through university managerial intelligence? (empirical studies at private Universities in East Java) - Siti Istikhoroh; Moeljadi P; Made Sudarma; Siti Aisjah (Cogent Business & Management, 2021)
This study aimed to identify and analyse the sustainability of private universities in East Java in terms of their ability to utilize knowledge-based strategic assets. The approach used was the quantitative approach (positivism), using a survey research method. The data obtained was number (score or value), analysed using statistical techniques called Structural Equation Models or SEM. The results of statistical testing were used to explain the relationship between variables, including Organizational Sustainability, Intellectual Capital, University Managerial Intelligence, and Social Media Marketing. From the data analysis, we concluded that a) Intellectual Capital has a positive and significant effect on the Sustainability of Private Higher Education Organizations in East Java, b) Intellectual Capital has a positive and significant effect on University Managerial Intelligence in Private Universities in East Java, c) University Managerial Intelligence has an effect on Organizational Sustainability of Private Universities in East Java, d) University Managerial Intelligence mediates the influence of Intellectual Capital on the Sustainability of Private Higher Education Organizations in East Java, e) Social Media Marketing does not moderate the influence of Intellectual Capital on the Sustainability of Private Higher Education Organizations in East Java, f) Social Media Marketing does not moderate the influence of University Managerial Intelligence on the Sustainability of Private Higher Education Organizations in East Java.
Keywords: 650; Social media marketing; moderating relationship; intellectual capital; organizational sustainability; private universities